Sharīʿah appraisal of the concepts of damān, taqṣīr,and taʿaddī in trust-based contracts (ʿuqūd al-amānāt) - Mohamed Naim, Asmadi; Md Hussain, Muhammad Nasri; Long, Muhamad Noor Habibi; Abu Bakar, Mahyuddin (King Abdulaziz University, 2016)
The study aims to examine the concepts of ḍamān (guarantee), taqṣīr (negligence) and taʿaddī (transgression) from Sharīʿah point of view and their relations with both trust-based contracts (ʿuqūd al-amānāt) and guarantee-based contracts (ʿuqūd al-ḍamānāt).The study conducted the qualitative research approaches which consist of documents analysis, interviews and observations in few phases. The study found that the fiduciary possessor should be held liable in a few cases; however it does not mean that it transformed the contract into a guarantee-based contract (ʿaqd al-ḍamānah) as it was under the rubric of ḍamān al-itlāf (indemnity for damage) or ḍamān al-yad (liability arising from possession on trust).